Analisis Komparasi Keakuratan Capital Asset Pricing Model (CAPM) dan Arbitrage Pricing Theory (APT) Dalam Memprediksi Return Saham pada Perusahaan Sektor Consumer Goods yang Terdaftar di Bursa Efek Indonesia - Nurul Izzah Maisyuri; Marlina Widiyanti; Kemas M. Husni Thamrin (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study was to determine the accuracy of the CAPM and APT models in predicting returns stock of companies in the sector for the consumer goods period 2017 to 2020 listed on the Indonesia Stock Exchange. The population of this study is all issuers of consumer goods stocks for the period January 2017 to December 2020 with a total sample of 23 companies. The selection of data samples in this study was carried out by purposive sampling. The data analysis technique was carried out using the test Mann Whitney. The results of the study and statistical tests showed that the MAPE APT was smaller than the MAPECAPM but the MAD values CAPM and MSECAPM were smaller than the MADAPT and MSEAPT, this means that the CAPM model is more accurate than the APT model because and there is no difference significant accuracy between CAPM and APT in predicting returns stock in the sector for the consumer goods period 2017 to 2020 on the Indonesia Stock Exchange. Keywords: Capital Asset Pricing Model, Arbitrage Pricing Theory, Mean Absolute Deviation (MAD), Mean Squared Error (MSE), Mean Absolute Percentage Error (MAPE).